Caries Experience, Periodontal Health, and Oral Hygiene in Pediatric Patients with Type 1 Diabetes Mellitus: A Comparative Cross-Sectional Study - Akgun, Semih Ercan; Guler, Derya; Kontbay, Tugba; Okumus, Irem; Oruc, Muhammet Ali; Yazıcıoglu, Bahadır; Tekin, Bahar (Aves, 2026)
Objective: To describe oral health status and its relationship with glycemic control in children with type 1 diabetes mellitus (T1DM) using standardized indices. Materials and Methods: A comparative cross-sectional study was conducted with 30 children aged 6-14 years with T1DM and 30 healthy controls. Oral examinations recorded DMFS/ dfs (Decayed, Missing, Filled Surfaces), PUFA/pufa (Pulpal involvement,Ulceration, Fistula, Abscess), Plaque Index (PI), Gingival Index (GI), and Simplified Oral Hygiene Index (OHI-S). Glycated hemoglobin (HbA1c) levels were categorized as <= 7% or >7%. Non-parametric tests, Spearman's correlation analyses were performed. The level of statistical significance was set at P < .05. Results: The T1DM group had significantly lower DMFS/dfs and PUFA/pufa scores than controls (P < .001 and P = .004, respectively), and no significant differences were found in PI, GI, and OHI-S values. In the T1DM group, correlation analyses between HbA1c levels and oral health indices (DMFS/dfs, PUFA/pufa, PI, GI, and OHI-S) revealed no statistically significant associations (P > .05). No statistically significant correlations were found between HbA1c and any of the oral health indices (P > .05). Conclusion: Children with T1DM showed lower caries experience, possibly due to regular medicalfollow-up, nutritional counseling, and improved oral hygiene. Routine oral health monitoringshould be integrated into pediatric diabetes care.
Keywords: Caries; children; dietary habits; HbA1c; oral health; periodontal indices; type 1 diabetes mellitus